Innovations adopted in the diagnosis of neuroendocrine tumors of the small intestine (Research, Society and Development, 2022)
Introduction: The small intestine is a rare site of neoplasms. Biological variations at the genetic level support the clinical heterogeneity of neuroendocrine tumors. Biomarkers have been indispensable in confirming any clinical suspicion of these tumors in the small intestine, due to the poor availability of other methods, and they are essential to assist in the differentiation of histological types. Objective: to verify the scientific productions about new technologies aimed at improving the diagnosis of neuroendocrine tumors of the small intestine. Methodology: This is an integrative literature review, whose database used was the Virtual Health Library, in which 8 articles published between 2017 and 2022 were selected. Discussion: Malignant neoplasms of the small intestine represent only 3% of malignancies of the differential treatment. May present with digestive bleeding such as melena, hematochezia or occult blood in the stool. Defining the etiology of the hemorrhage can be a challenge depending on the topography. Currently, videocapsule endoscopy, an innovative method that allows endoscopic investigation of the segment in question, is an alternative. Serum biomarkers such as Chromogranin A, 5-hydroxyindole-acetic acid are already well established, and mapping the action of NRP-2 and PD-1 receptors is promising. Conclusion: Imaging methods are currently the main diagnostic tool. With the help of the study of miRNA bases, it is possible that in the future a useful marker in the screening of neuroendocrine tumors will be obtained. NRP-2 and PD-1 receptors have been shown to participate in important biochemical and immunological pathways for the regulation of tumor activity.